Influence of moonpool on the total resistance of a drillship by the effect of water motions inside the moonpool - Ponnappan, Sivabalan; Sankunny, Surendran (Sustainable Marine Structures, 2019)
Moonpools are openings right through the hull from continuous deck to bottom of the ship, allowing equipment or mini-submarines to be put into the water at a location on the vessel with minimum ship motion. Open moonpools in a drillship are causing additional resistance when the ship is in forward speed. It was shown that the water inside the moonpool started to oscillate at forward speed. The water mass in the moonpool is subjected to sloshing and piston modes. The vertical motion is piston mode and the longitudinal one is called as sloshing mode. This water particle motion inside the moonpool is mainly depended on the geometry, moonpool depth, and encountered wave frequency. Out of this, moonpool geometry is one of the key factors for the performance of the moonpool. The varying cross-section geometry is one of the practically possible and economically feasible solutions to reduce the oscillation to a considerable level is attempted in this paper. Also the resistance caused by the moonpool and the free surface generated around the hull is investigated with the use of computer simulation. ER